ISU-ISU KONTEMPORER DALAM KONSTRUKSI PEMBAHARUAN PESANTREN - Faisal Kamal (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
Pesantren as the oldest institution of Islamic education in Indonesia was instrumental in advancing the development of education of Indonesia. Today, the development of pesantren education showed significant progress. Marked by a growing number of religious schools that do updates from various aspects, such as the innovation of curriculum, management, leadership and learning methods. Pesantren known as traditional educational institutions demonstrate a progressive attitude by making various changes and innovation in an effort to advance the educational system. This positive trend break skepticism among which assumed that pesantren as the anti-Islamic institution changes. The issues confronting the pesantren such as secularism, the dichotomy of education, and globalization which affect the pesantren education changes. This article specifically discusses such issues through the analysis of the literature review. Pesantren as Islamic educational institutions are expected to move forward as the advance of the times. Pesantren as an educational institution of Islam by remaining principled tradition and characteristic and open to renewal.